ESTABELECIMENTO DE FORRAGEIRAS HIBERNAIS SOBRESSEMEADAS EM PASTAGEM DE TIFTON 85 MANEJADA SOB PASTEJO - Londero, Ana L.; Konradt, Guilherme; Farias, Joana d. M.; Ost, Henrique J.; Bortolin, Felipe; Maixner, Adriano R.; Uhde, Leonir T.; Sartori, Cesar O.; Fernandes, Sandra B. V.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo